Facial venous malformation with phleboliths - Sahar A. Alsadah; Wala S. Alshiha; Nasser Assiri; Haifa Alnasser (Elsevier, 2020)
we herein report a case of unusual presentation of pediatric cheek mass.where we had 5 years old girl presented with right cheek mass which was asymptomatic except for facial asymmetry noticed by the family.upon physical exam it was 3 × 4 cm hard fixed mass.imaging study reveal typical characteristics of venous malformation with phleboliths.which underwent surgical excision.post operation follow up revealed hematoma which was managed by drainage. Venous malformation with phlebolith is a rare entity with MRI being the diagnostic modality. management should be tailored in case to case basis.